The Predictive Role of Temperamental Traits and Inhibitory- Control Skills on Ego Resiliency of Preschool Children - (:unkn) unknown (My University, 2018)
Ego resiliency means positive development tendency despite risk factors. Resilient children areexpected to cope with individual, familial and environmental risk factors, so developing resiliency could beaccepted as a developmental task for children. The aim of the study is to investigate the predictive role oftwo selected individual variables; inhibitory control skills and temperament characteristics of preschoolchildren, on their ego resiliency levels. The study is in survey method. The sample of the study includes 55-73 months old 78 children, who attend preschools. The data collection tools that are used in this study are;The Personal Information Form, The Short Temperament Scale for Children and Children’s Ego ResiliencyScale (Mother Form). Also two tasks, named as Green-Red Signs and Touch Your Toe were used to assesspreschoolers’ inhibitory control skills. When all the variables are considered together in the regressionanalysis, it has been found that the inhibitory control skills are significantly predictive of children's egoresiliency, but temperamental characteristics are not.

Ego sağlamlığı risk faktörlerine rağmen olumlu gelişim eğilimini ifade etmektedir. Ego sağlamlığına sahip çocukların bireysel, ailesel ve çevresel risk faktörleri ile baş etmeleri beklenmektedir, bu nedenle de ego sağlamlığı geliştirmek çocuklar için bir gelişim görevi olarak kabul edilebilir. Bu araştırmanın amacı, bireysel boyutta seçilmiş iki değişkenin, öz kontrol becerileri ve mizaç özellikleri, ego sağlamlık düzeyleri üzerindeki yordayıcı rolünü araştırmaktır. Araştırma tarama modelinde tasarlanmıştır. Araştırmanın örneklemini, yaşları 55-73 aylar arasında olan okul öncesi eğitim kurumlarına devam eden 78 çocuk oluşturmaktadır. Kişisel Bilgi Formu, Çocuklar için Kısa Mizaç Ölçeği ve Çocuk Ego Sağlamlığı Ölçeği (Anne Formu) araştırmada kullanılan veri toplama araçlarıdır. Ayrıca çocukların öz kontrol becerilerini değerlendirmek için Yeşil-Kırmızı İşaretler ve Ayak Parmağına Dokun görevleri kullanılmıştır. Regresyon analizi ile tüm değişkenlerin birlikte etkisine bakıldığında, öz kontrol becerilerinin çocukların ego sağlamlık düzeylerinin anlamlı bir yordayıcısı olduğu, fakat mizaç özelliklerinin yordayıcı etkisinin olmadığı bulunmuştur.
Mizaç Özellikleri ve Öz Kontrol Becerilerinin Okul Öncesi Dönem Çocuklardaki Ego Sağlamlık Düzeyini Yordayıcı Rolü
Keywords: Eğitim, Eğitim Araştırmaları